From Import Dependency to Energy Self-Reliance: Nepal’s Policy Push Towards Renewable Energy Solutions (Janapriya Journal of Interdisciplinary Studies, 2025)
Nepal’s energy transition highlights the challenges of shifting from fossil fuel dependence to renewables despite generating over 90% of its electricity from hydropower. Heavy reliance on imported petroleum for transport (52%) and industry (28%) exposes the country to economic and geopolitical risks, as seen during the 2015 fuel blockade. While policies like the National Renewable Energy Policy (2011) improved rural electrification, barriers such as high costs, weak infrastructure, and limited solar/wind adoption hinder progress. This study applies Dependency Theory and Energy Transition Theory to analyze Nepal’s energy landscape, emphasizing the socio-political dimensions of the shift. It proposes the Integrated Renewable Transition Model (IRTM), combining policy reforms, financial mechanisms (e.g., green bonds), hybrid energy systems, and community engagement. Strategies include renewable quotas for industries, promoting electric vehicles, and leveraging international climate funds. Achieving energy self-reliance requires holistic reforms across transport, industry, and households, aligning with global sustainability goals. Nepal’s experience offers lessons for developing nations, demonstrating that strategic planning and collective action can foster a resilient, low-carbon future.